Prestasi Mahasiswa Berstatus Nikah pada Masa Studi di Universitas Islam Sumatera Utara - Anggraini, Mutia; Maulana, Mohammad Firman; Sumiati, Sumiati (Lembaga Yasin AlSys, 2024)
This study aims to explore the motivations, impacts, and academic achievements of students who marry while pursuing their studies at the Universitas Islam Sumatera Utara. The research uses a qualitative approach with data collection through interviews, observations, and documentation. Primary data was obtained from interviews with five students who married during their studies, while secondary data was gathered from relevant literature and journals. The findings reveal that the main motivations for students to marry during their studies are to avoid zina (adultery), uphold religious commitments, and prepare for family life. The impact of marriage includes difficulties in balancing study time with household responsibilities, but students report receiving positive emotional support from their spouses. On the other hand, some students face challenges in completing their studies on time and experience disagreements with their spouses. Their academic achievements vary, with some students graduating on time, although there were delays in thesis work and class attendance. This study provides insights into the challenges and opportunities faced by married students, as well as the importance of social support and effective communication with spouses to overcome these obstacles.